Pencegahan Kecacatan Akibat Kusta di Kota Manado - Wewengkang, Kevin; Palandeng, Henry M. F.; Rombot, Dina V. (UNIVERSITAS SAM RATULANGI, 2016)
Leprosy is an infectious disease caused by the bacteria Mycobacterium leprae. Based on data from the Ministry of Health new cases of leprosy in Indonesia in 2013 and 2014. there were 16.856 and 16.131 new cases respectively. North Sulawesi ranks sixth among the provinces with the numbers highest Case Detection Rate (CDR) per 100,000 population in Indonesia , which is 14.65 per 100,000 population. Registered patients in the city of Manado in 2013 and 2014 there were 67 and 69 people respectively. Leprosy disability level 2 in the city of Manado is quite high, reaching 10.6%. Disability due to leprosy can be prevented. Leprosy patient behavior plays an important role in the prevention of disability due to the disease itself. This study aimed to describe the behavior of leprosy patients in the prevention of disability due to leprosy. This study is a qualitative descriptive study with cross sectional study design. Data collected by in-depth interview techniques and triangulation with samples of 9 people with leprosy patients using purposive sampling. The results showed that the majority of informants knowledge about leprosy in general still lacking, but knowledge in the prevention of disability through regular treatment is sufficient. The attitude of the informants was good and optimistic with the treatment, showed a positive attitude. Most of the actions of the informants in the prevention of disability as a regular treatment has been good, although still need to be optimized. The behavior of the informants was good overall, but knowledge about leprosy in general needs to be improved further. Patients are advised to more actively seek information about the disease and prevention of disability, as well as the necessity for improved education and health promotion concerning leprosy by the health workers.